Immunohistochemical expression of core 2 β1, 6‐N‐acetylglucosaminyl transferase 1 (C2GnT1) in endometrioid‐type endometrial carcinoma: a novel potential prognostic factor. Issue 7 (26th April 2013) - Miyamoto, Tsutomu; Suzuki, Akihisa; Asaka, Ryoichi; Ishikawa, Kaori; Yamada, Yasushi; Kobara, Hisanori; Nakayama, Jun; Shiozawa, Tanri
Abstract : Aims: It has been reported that the expression of core 2 β1, 6‐ N ‐acetylglucosaminyl transferase 1 (C2GnT1), which synthesizes the core 2 branching structure on O ‐glycans, may be associated with the biological aggressiveness of tumour cells. Therefore, the aim of this study was to examine the relationship between the expression of C2GnT1 and clinicopathological parameters of patients with endometrial carcinoma. Methods and results: The immunohistochemical expression of C2GnT1 was examined in 84 cases of endometrioid‐type endometrial carcinoma, 15 cases of endometrial hyperplasia, and 30 normal endometria. The staining intensity was reported according to a positivity index (PI, full score 100), calculated from the percentage of positive cells. The expression of C2GnT1 was significantly higher in endometrial carcinoma (PI = 8.31 ± 15.29) than in normal endometrium (PI = 0.52 ± 1.24) ( P  < 0.0005). In carcinomas, the PI was higher in high‐grade or advanced‐stage tumours, but not significantly. Topologically, C2GnT1 was strongly expressed at sites of deep myometrial invasion. In addition, patients with C2GnT1 overexpression (PI ≥ 10) had significantly shorter survival ( P  < 0.0005). Multivariable analysis also indicated that C2GnT1 overexpression was an independent prognostic factor ( P  = 0.017). Conclusions: C2GnT1 appears to be involved in the biological aggressiveness of endometrial carcinoma. C2GnT1 might become a novel prognostic factor for endometrial carcinoma.